Aid, debt burden and goverment fiscal behaviour: A new model applied to Côte d'Ivoire - Mark McGillivray; Banzoumana Ouattara (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper examines the impact of foreign aid on public sector fiscal behaviour in Côte d'Ivoire. A special interest is the relationship between aid, debt servicing and debt, given that Côte d'Ivoire is a highly indebted country. The theoretical model employed differs from those of previous studies by highlighting the interaction between debt servicing and the other fiscal variables. This model is estimated using 1975–99 time series data. Key findings are that the bulk of aid is allocated to debt servicing and that aid is associated with increases in the level of public debt.
Keywords: C32; F35; H20; H50; H63; 330; Côte d'Ivoire; foreign aid; public sector fiscal behaviour; taxation; debt; debt servicing; Entwicklungshilfe; Finanzpolitik; Elfenbeinküste